2012
DOI: 10.1021/es302420z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Recycling on Cradle-to-Gate Energy Consumption and Greenhouse Gas Emissions of Automotive Lithium-Ion Batteries

Abstract: This paper addresses the environmental burdens (energy consumption and air emissions, including greenhouse gases, GHGs) of the material production, assembly, and recycling of automotive lithium-ion batteries in hybrid electric, plug-in hybrid electric, and battery electric vehicles (BEV) that use LiMn(2)O(4) cathode material. In this analysis, we calculated the energy consumed and air emissions generated when recovering LiMn(2)O(4), aluminum, and copper in three recycling processes (hydrometallurgical, interme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
226
2
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 358 publications
(234 citation statements)
references
References 13 publications
3
226
2
3
Order By: Relevance
“…High collection rates and that almost all material is recovered to virgin quality have been assumed (Van den Bossche et al 2006). The potential for such recycling of lithium-ion batteries, which is both energy efficient and has high recovery rate, has been investigated in several papers (Dunn et al 2012;Gaines et al 2011;Li et al 2013;Sullivan et al 2011). However, only in the case of lead acid batteries are highly efficient recycling processes currently in practice.…”
Section: Weighted Results For Batteries and Recyclingmentioning
confidence: 99%
See 2 more Smart Citations
“…High collection rates and that almost all material is recovered to virgin quality have been assumed (Van den Bossche et al 2006). The potential for such recycling of lithium-ion batteries, which is both energy efficient and has high recovery rate, has been investigated in several papers (Dunn et al 2012;Gaines et al 2011;Li et al 2013;Sullivan et al 2011). However, only in the case of lead acid batteries are highly efficient recycling processes currently in practice.…”
Section: Weighted Results For Batteries and Recyclingmentioning
confidence: 99%
“…Battery manufacturing, based on a study by Majeau-Bettez et al (2011), is pointed out as an important explanation. Actually, Dunn et al (2012) have investigated the difference between the values reported by Majeau-Bettez et al (2011) and Notter et al (2010a), and observed that the energy used to manufacture specific battery subcomponents is more than 1 order of magnitude larger in the study by Majeau-Bettez et al In trying to explain the cause, Dunn et al (2012) found that studies which use a more detailed "process level" approach to the life cycle inventory, as Notter el al., produce much lower values ). An average vehicle lifetime of 230,500 km corresponding to 13.7 years has been used, based on statistical data from the Belgian vehicle registration database.…”
Section: Energy Demand Of Materials Production and Equipment Manufactumentioning
confidence: 99%
See 1 more Smart Citation
“…The SOCR for the wirelessly charged battery is the same as that of the plug-in charged battery (60%). The battery weight (kg) can be calculated by dividing the battery capacity (kW h) by the battery specific energy (0.13 kW h per kg of Li-ion battery) [29]. Therefore, the percentage of vehicle mass reduction due to primary downsizing can be determined, relative to a bus of 15 t, comprising the assumed curb weight of 14 t [4] and the constant average weight of 1 t for driver, passengers and cargo [30].…”
Section: Battery Downsizing and Lightweighting Calculationmentioning
confidence: 99%
“…LMO was chosen because of its well established life cycle inventory, lower cost and abundance of manganese in nature [35,36]. The cradle-to-gate energy and GHG emissions are modeled as 75 MJ/kg battery and 5.1 kg CO 2 -eq/kg battery, according to a process LCA study of LMO batteries for electric vehicles that is specific to the United States [29]. When the OSM is 5%, RSC is 15% and NOR is 20%, the SOCR is 60% with the state of charge (SOC, %) assumed to swing around 35-95% for both plug-in and wirelessly charged batteries [28].…”
Section: Inputmentioning
confidence: 99%